Coaxial semi-solid extrusion and ionotropic alginate gelation: A successful duo for personalized floating formulations via 3D printing. (15th May 2021) - Falcone, Giovanni; Saviano, Marilena; Aquino, Rita P.; Del Gaudio, Pasquale; Russo, Paola
Graphical abstract: Highlights: Fused Deposition Modelling prototyping of functional microfluidic extruders. Innovative one-step process for alginate ionotropic gelation in coaxial 3D printing. Optimal extrudability range up to 105° shape-retention angle values. No impact on drug content (43%) and efficiency (85%) of different digital models. Similar release kinetics confirm the potential application in dosage personalization. Abstract: With the aim to fulfill the patient-centered approach of precision medicine, in this research, innovative floating drug delivery systems have been developed through the use of alginate matrix and fully characterized. Particularly, to exploit the ionotropic gelation of alginate, a customized coaxial extruder for Semi-solid Extrusion 3D printing, has been used for the simultaneous dispensing of ink gel (sodium alginate 6% w/v) and crosslinking gel (hydroxyethyl cellulose 3 %w/v, calcium chloride 0.1M and Tween 85 0.1% v/v). The latter also loaded with Propranolol Hydrochloride 12.5%w/v. A novel single-step process gelation for the extemporaneous gelation of loaded oral systems has been therefore developed. These technologically advanced formulations showed high printing reproducibility in manufacturing different models (mass of a single layer 535.41 ± 40.00 mg with an average drug loading efficiency of 85% w/w) and similar release behavior, paving the way for their customization in terms of drug dosages via this pioneering process.